PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING STUDI PADA DINAS PARIWISATA KABUPATEN GUNUNGKIDUL - Rio Muhammad Febriansyah; Kusuma Chandra Kirana; Epsilandri Septyarini (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
This study aims to examine the influence of transformational leadership styles and work environment on employee performance with work motivation as an intervening variable to employees within the tourism office of Gunungkidul Regency. This type of research uses quantitative research methods based on positivistic, where research data uses numbers that will later be measured with statistics as a calculation test tool and related to the problem to be studied to produce a conclusion. To obtain data, researchers using the Simple Random Sampling approach were given to 85 selected employees. This study used the T test and the Sobel test to test from the hypothesis. The results of this study show that partially the variables of transformational leadership style and work environment have a positive and significant effect on the performance of employees, transformational leadership styles and work environments partially have a positive and significant effect on work motivation, and work motivation is able to mediate between transformational leadership styles and work environments on employee performance.